An Interactive Swift Programming Language E-Learning Platform For Ios Application Development - Lye, Boon Jet (2021)
Swift programming language is a famous programming language that is adopted by lots of developers to develop iOS, iPadOS, macOS, tvOS and watchOS applications as it is modern, fast and safe. However, Mac and iPad are usually required to learn Swift programming language and there’s no existing Swift programming languagecentric learning platform for learners. Therefore, this project is to develop an interactive Swift programming language e-learning platform for students. This platform can let students read materials, do exercises and graded quizzes, write codes in the embedded online code editors, view profiles, and chat with other online users. It also allows administrators to modify the course content, chat with students, as well as manage student’s accounts and view student performance. Evolutionary prototyping has been adopted as the software development methodology to implement systems in several iterations. Requirements were gathered by looking at literature reviews. 12 students and 1 lecturer from UECS3263 iOS Application Development course have been chosen to test the system which was hosted in the web hosting services. A system usability score of 84.43 had been obtained from the tester’s response. In short, all objectives were achieved and the platform was opened to all students who registered UECS3263 iOS Application Development in the May 2021 trimester.